Personality disorders in medical students: Measuring by IPDE-10 - Nahathai Wongpakaran (2018)
Objectives: The purpose of the present study was to investigate the personality disorders(PDs) of fifth year medical students of Chiang Mai University according to International Classification of Disease -10 (ICD-10) system by using IPDE-10. Material and Method: A group of ninety-nine out of 150 of fifth-year medical students of Chiang Mai University undertook personality disorder inventory - International Personality Disorder Examination ICD-10 screening questionnaires (IPDE-ICD 10). Those who received diagnoses of personality disorders were subsequently interviewed by the authors to find definite diagnoses. Results: The prevalence rate of PDs was 9%. The proportion of all PDs was as follows; 1%, 3%, 2%,2%, and 1% for paranoid, impulsive, histrionic, anankastic, and dependent, respectively. The rate of probable diagnoses of PDs ranged from 1%-22.8%. Conclusion: The prevalence rate found in the medical students group did not differ from that in other populations. The benefit of ICD diagnosis system was discussed.